ANALYSIS OF CASH AUDIT PROCEDURES AT KAP KUMALAHADI, SUGENG PAMUDJI & REKAN BANDUNG BRANCH - Raeni Putri Sari; Muhammad Ubaidillah; Imam Prayogo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The background of this study is based on the importance of cash audits as the most liquid assets that are vulnerable to the risk of deviation. The purpose of the study is to determine the general audit procedures and cash audit procedures applied at KAP Kumalahadi, Sugeng Pamudji & Partners Bandung Branch, and to compare them with existing theories. This study uses a qualitative approach with data collection methods through observation, interviews, and documentation studies. The analysis was carried out by comparing cash audit practices at KAP (including cash opname, bank confirmation, and reconciliation) with standard theory. The results of the study indicate that cash audit procedures KAP Kumalahadi, Sugeng Pamudji & Partners Bandung Branch have been implemented well and according to standards, although there are some differences in their implementation. Cash opname and bank confirmation practices are carried out in more detail and systematically than theory.